Breast cancer and depression: issues in clinical care (Faculty of Medicine Universitas Indonesia, 2012)
Many of breast-cancer patients experience distress and most of them experience depression which may lead to amplification of physical symptoms, increased functional impairment, and poor treatment adherence. We did a review on available literature from PubMed about prevalence, distress magnitudes, coping styles, and treatment methods of major depression in women with breast cancer from 1978 to 2010. Diagnosis and treatment of depressive episodes in women with breast cancer is challenging because of overlapping symptoms and co morbid conditions. Major depression is often under-recognized and undertreated among breast cancer patients. This review highlighted the issues on identifying and managing depression in breast cancer patients in clinical settings. (Med J Indones. 2012;21:240-6)